The Smithian–Spathian boundary in North Greenland: implications for extreme global climate changes. (19th October 2020) - Lindström, Sofie; Bjerager, Morten; Alsen, Peter; Sanei, Hamed; Bojesen-Koefoed, Jørgen
Abstract: Smithian–lower Anisian strata in Peary Land, North Greenland, were deposited at ∼45° N on the northern margin of Pangaea in offshore to upper shoreface settings. The well-constrained succession (palynology and ammonite biostratigraphy) documents a remarkable shift from lycophyte spore-dominated assemblages in the upper Smithian to gymnosperm pollen-dominated ones in the lower Spathian in concert with a marked shift of +6 ‰ in δ 13 Corg . Correlation with other Smithian–Spathian boundary sections that record terrestrial floral changes indicates that the recovery of gymnosperms began earlier in the mid-latitudes of the Southern Hemisphere than in the Northern Hemisphere. The lycophyte-dominated Late Smithian Thermal Maximum is here interpreted as reflecting dry and hot climatic conditions with only brief seasonal precipitation unable to sustain large areas of gymnosperm trees, but able to revive dehydrated lycophytes. This suggests that the Late Smithian Thermal Maximum was a time of widespread aridity, which is also supported by red bed deposition in many areas globally, even as far south as Antarctica. The shift to gymnosperm-dominated vegetation during the cooling across the Smithian–Spathian boundary reflects a change to seasonally more humid climatic conditions favouring gymnosperm recovery, and could have been initiated by increased albedo over land due to the widespread aridity during the Late Smithian Thermal Maximum. The recovery of gymnosperm vegetation would have helped to draw down CO2 from the atmosphere and exacerbate global cooling.